GIS-based scheduling and monitoring irrigation delivery for rice irrigation system: Part II. Monitoring - Rowshon, M.K.; Kwok, C.Y.; Lee, T.S. (Elsevier, 2003)
A computer program with a geographical information system (GIS)-based user-interface was developed to monitor the delivery of irrigation water. The irrigation indices relative water supply (RWS) and cumulative relative water supply (CRWS) were used. The weekly water balance were used to compute these irrigation indices using the recommended irrigation supply given by scheduling program at secondary off-takes regulated by constant head orifices (CHOs) and feedback data at the field level. These computations provide information on the uniformity of water distribution and any shortfall or excess. The program is intended to characterize the irrigation delivery performance on a previous week basis and what decisions to adopt for the next. The weekly results of RWS ranged from 1.01 to 2.24 during the main season, and from 1.01 to 1.87 during the off-season respectively for 1997. The results are displayed allowing the manager to view maps, tables and graphs in a comprehensible form to ease decision-making on water management as the season progresses. © 2003 Elsevier Science B.V. All rights reserved.